LC3B in Malignant Cells Correlates With Immune Infiltrate in Hypopharyngeal Squamous Cell Carcinoma - Sifan Gao MM (Technology in Cancer Research & Treatment, 2020)
The objective of this study was to investigate the between autophagy activity and local immune response in hypopharyngeal squamous cell carcinoma (HSCC). Herein, we observed the expression of autophagy marker microtubule-associated protein light chain 3B (MAP1LC3B), CD8 cytotoxic T lymphocytes (CTLs), CD39 (regulatory T cells Tregs) and CD163 (tumor-associated macrophages TAMs) in HSCC, and determined the prognostic roles of CD8 + /CD39 + and CD8 + /CD163 + in patients with HSCC. The expression of light chain 3B (LC3B) and CD8 + /CD39 + was found to be significantly lower in HSCC tissues than in adjacent non-tumor mucosa tissue samples; LC3B expression was positively correlated with the infiltration rate of CD8 + /CD39 + in HSCC. Further studies revealed that the ratio of CD8 + /CD39 + immune cells was negatively correlated with tumor lymph node metastasis and TNM classification, while the ratio of CD8 + /CD163 + immune cells was negatively correlated with TNM classification. Moreover, the expression of LC3B was analyzed and the patients were grouped according to their immune infiltration characteristics. The 5-year cumulative survival rates of LC3B + , CD8 + /CD39 + , and CD8 + /CD163 + patients were significantly higher than those of other group patients. Collectively, our studies indicated that the expression of LC3B in HSCC was correlated with the infiltration ratio of immune cells, and a change in autophagy activity may affect the cellular immunity in HSCC. The ratios of tCD8 + /CD39 + and tCD8 + /CD163 + may serve as prognostic factors for HSCC.